Book of Changes – from doubt to fractality and free will (Research Announcements "Heritage BG", 2025)
The Book of Changes is one of the oldest written sources for philosophy. The Bulgarian calendar is a unique part of our ancient intangible heritage. The connections of fractal geometry with various fields of science are expanding. Combining these elements into a logical system manages to use the common points of contact to enhance the understanding of each one, as well as to reflect on human doubt and free will. References:Bankova 2024: Bankova, Petya. Detski igri. Balgarska Etnografia, https://balgarskaetnografia.com/jiznen-cikal/detstvo/detski-igri.html, Accessed 26 June 2024.Bulgarian calendar 2024: Balgarskiyat calendar, https://bgkalendar.com/kalendar-bg.php?lang=bg, Accessed 26 June 2024.Doncheva, Ilieva 2014: Doncheva, Julia, Ilieva, Iskra. Balgarskite folklorni igri v detskata gradina i nachalnoto uchilishte. Nauchni trudove na Rusenskia universitet 53: 126-130. Ruse, 2014.Drumev 2017: Drumev, Dobromir.Boyni izkustva. Razmisli na Sensey Stefan Hinkov. Kibea, Sofia, stranitsi 512, ISBN 9789544747749. Sofia, 2017.History of the Bulgarians 2024: Istoria na balgarite., https://historybg.info/, Accessed 26 June 2024.Ivanova 2005: Ivanova, Zlatina. Liturgia sled liturgiyata, Dveri na pravoslavieto, https://dveri.bg/component/com_content/Itemid,51/catid,63/id,508/view,article/, Accessed 26 June 2024.Vezenkov 2015: Vezenkov, Stoyan. Svobodniyat izbor v konteksta na problema „ezik-tyalo“. Filosofia 24.3: 298-305. Filosofia, Sofia, 2015.Bellavita 2006: Bellavita, Christopher. Changing homeland security: Shape patterns, not programs. Homeland Security Affairs 2.3: 1-21.Britannica 2024: Britannica, The Editors of Encyclopaedia. ‘Chaos theory’. Encyclopedia Britannica, 1 Jun. 2024, https://www.britannica.com/science/chaos-theory. Accessed 26 June 2024.Browning, Boudes 2005: Browning, Larry, Boudes Thierry. The use of narrative to understand and respond to complexity: A comparative analysis of the Cynefin and Weickian models. E: CO 7.3-4: 32-39.Carus 1910: Carus, Paul. Person and personality. In: Hegeler, Edward C. (ed.). The Monist. Vol. 20. Chicago: Open Court Publishing Company. p. 369.Fernбndez, Jelinek 2001: Fernбndez, Eduardo, Jelinek, Herbert F. Use of Fractal Theory in Neuroscience: Methods, Advantages, and Potential Problems, Methods, Volume 24, Issue 4, Pages 309-321, ISSN 1046-2023, https://doi.org/10.1006/meth.2001.1201.Fractal foundation 2024: What are fractals? https://fractalfoundation.org/resources/what-are-fractals/, Accessed 26 June 2024.Hacker, Moore 2023: Hacker, Edward, Moore, Steve. I Ching: An Annotated Bibliography. Routledge.Hartung 2013: Hartung, Christopher. Thomas Aquinas on free will. Spring. Ph.D Dissertation, University of Delaware.Hershock 1991: Hershock, Peter D. The Structure of Change in the I CHING. Journal of Chinese Philosophy 18.3: 257-285.Huang 2010: Huang, Taoist Master Alfred. The Complete I Ching—10th Anniversary Edition: The Definitive Translation by Taoist Master Alfred Huang. Simon and Schuster.Mandelbrot 1989: Mandelbrot, Benoit B. Fractal geometry: what is it, and what does it do?. Proceedings of the Royal Society of London. A. Mathematical and Physical Sciences 423.1864: 3-16.Seidenberg 1965: Seidenberg, A. The sixty system of sumer. Archive for History of Exact Sciences, 2(5), 436-440.Smith 2012: Smith, Richard J. The I Ching: A Biography, Princeton: Princeton University Press, 2012. https://doi.org/10.1515/9781400841622Sturmberg, Martin 2008: Sturmberg, Joachim P., Martin, Carmel M. Knowing – in Medicine. Journal of Evaluation in Clinical Practice, № 14: 767-770. https://doi.org/10.1111/j.1365-2753.2008.01011.xRössler 1976: Rössler, Otto E. Different types of chaos in two simple differential equations. Zeitschrift fьr Naturforschung A 31.12 (1976): 1664-1670.Rudd, Dixon 2013: Rudd, Richard, Dixon, Jennifer M. Gene Keys. Watkins Publishing.Walter 1995: Walter, Katya. Nonlinear Computation in the I Ching. Advances in Human Factors/Ergonomics. Vol. 20. Elsevier. 1053-1057.Westphal 2007: Westphal, Merold. The importance of overcoming metaphysics for the life of faith. Modern Theology 23.2: 253-278.Xutong 2024: Xutong, LI, Object of i ching. Academia.edu, Accessed 26 June 2024.Zheng, Cao 2023: Zheng, Xinqi, Cao, Yang. Big data reveals the change characteristics of 64 hexagrams and lines. Preprints 2023080208. https://doi.org/10.20944/preprints202308.0208.v1
Keywords: I Ching; Bulgarian; calendar fractal; doubt; free will